INSTITUTION LEVEL FINANCIAL APPLICATION SYSTEM AND INTERNAL CONTROL OF THE QUALITY OF GOVERNMENT FINANCIAL REPORTS WITH THE QUALITY OF HUMAN RESOURCES AS A MODERATION VARIABLE - SULAEMAN; Mediaty; Kusumawati, Andi (International Journal of Multidisciplinary Research and Studies, 2023)
This study aims to examine the Effect of Institutional Level Financial Application Systems and Internal Control over Financial Reporting on the Quality of Government Financial Reports with the Quality of Human Resources as a Moderating Variable. This study uses a quantitative approach. This study uses primary data collected through questionnaires from 83 respondents who are working unit financial report preparation officers in the working area of the Poso KPPN, Central Sulawesi Province. Data analysis using Smart PLS. The results showed that the Financial Application System at the Agency Level and Internal Control over Financial Reporting had a positive effect on the Quality of Government Financial Reports. The quality of human resources as a moderating variable in this study strengthens the effect of the Agency Level Financial Application System and Internal Control over Financial Reporting on the Quality of Government Financial Reports.